Causal Nexus Between Foreign Direct Investment and Economic Growth in India - Srinivasan, P. (Indian Journal of Finance, 2010)
Foreign Direct Investment (FDI) is widely viewed as an important catalyst for the economic transformation of the transition economies. The most widespread belief among researchers and policy makers is that FDI boosts growth through different channels. They increase the capital stock and employment, stimulate technological change through technological diffusion and generate technological spillovers for local firms. As it eases the transfer of technology, foreign investment is expected to increase and improve the existing stock of knowledge in the recipient economy through labour training, skill acquisition and diffusion. It contributes to introduce new management practices and a more efficient organisation of the production process, which in turn improves the productivity of host countries and thus stimulates economic growth.